2020
DOI: 10.2147/ott.s236854
|View full text |Cite
|
Sign up to set email alerts
|

<p>GAS2 Promotes Cell Proliferation and Invasion and Suppresses Apoptosis in Pediatric T-Cell Acute Lymphoblastic Leukemia and Activates Wnt/β-Catenin Pathway</p>

Abstract: Purpose: This study aimed to investigate the effect of growth arrest specific 2 (GAS2) on T-cell acute lymphoblastic leukemia (T-ALL) and its potential molecular mechanism. Methods: The GAS2 expression level was detected by qRT-RCR and Western blot in normal T lymphocytes and TALL cells Jurkat and CCRF-CEM. The proliferation and invasion of Jurkat and CCRF-CEM cells were detected by MTT and Transwell assay, respectively. Apoptosis and cell cycle were measured by flow cytometry. In addition, the chemotherapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 33 publications
(36 reference statements)
1
19
0
Order By: Relevance
“…A large number of antitumor natural compounds, such as baicalin and homoharringtonine, have demonstrated to induce cell death and apoptosis in close association with cell cycle arrest at the G 1 phase (31,32). Notably, the present study demonstrated that Jurkat cells treated with linalool had reduced cell accumulation at the G 0 /G 1 phase, which contains numerous non-proliferating leukaemia cells (33). The findings of the present study indicate that linalool may affect proliferating and non-proliferating T-ALL cells.…”
Section: Discussionsupporting
confidence: 47%
“…A large number of antitumor natural compounds, such as baicalin and homoharringtonine, have demonstrated to induce cell death and apoptosis in close association with cell cycle arrest at the G 1 phase (31,32). Notably, the present study demonstrated that Jurkat cells treated with linalool had reduced cell accumulation at the G 0 /G 1 phase, which contains numerous non-proliferating leukaemia cells (33). The findings of the present study indicate that linalool may affect proliferating and non-proliferating T-ALL cells.…”
Section: Discussionsupporting
confidence: 47%
“…GAS2 protein has been reported to promote the growth of several leukaemic cells, such as K562, MEG-01, Jurkat or THP-1 cells. 36,48,51 Further, GAS2 can facilitate the tumour formation of THP-1 cells in nude mice. 51 GAS2 is reportedly involved in the disease transformation of CML 52 and exhibits an opposite effect on the inhibition or emergency granulopoiesis termination roles of ICSBP for leukaemia.…”
Section: Gas2l3mentioning
confidence: 95%
“…13,35 In contrast, GAS2 in two T-cell acute lymphoblastic leukaemia cell lines (Jurkat and CCRF-CEM) facilitates the G1-to-S transition of the cell cycle. 36 To date, limited experimental evidence has been found linking the GAS2 family members with the cell cycle. For example, overexpression of GAS2L1 was reported to lengthen the cell cycle and inhibit the growth of stem cell factor/erythropoietin (SCF/EPO)-dependent red cell progenitors.…”
Section: Cell Cyclementioning
confidence: 99%
See 2 more Smart Citations